CDIO And The Engineering Of Personalised Learning Environment: An Exploration - Raihanah M.M.; Norhana Arsad; Mohd Muzhafar Idrus (Science Publication Corporation, 2024)
International Journal of Engineering & Technology, 8 (1.2) (2019) 194-198